2010
DOI: 10.1075/intp.12.1.03lee
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting reported speech in witnesses’ evidence

Abstract: Drawing on the discourse of interpreter-mediated examinations of Koreanspeaking witnesses in an Australian courtroom, this paper explores court interpreters' renditions of reported speech contained in witnesses' evidence. Direct reported speech is generally preferred in the courtroom because of the evidentiary rule against the admission of hearsay. However, Korean-speaking witnesses who are not familiar with this rule and with the discursive practices of the court tend to use indirect reported speech. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Indeed, the results of a national survey of judicial officers and interpreters in Australia showed that both groups prefer to use direct speech (Hale 2011). It is therefore interesting to note reported cases of interpreters alternating between direct and reported speech (Angermeyer 2009;Cheung 2012;Lee 2010).…”
Section: Direct Speech In Court Interpretingmentioning
confidence: 96%
“…Indeed, the results of a national survey of judicial officers and interpreters in Australia showed that both groups prefer to use direct speech (Hale 2011). It is therefore interesting to note reported cases of interpreters alternating between direct and reported speech (Angermeyer 2009;Cheung 2012;Lee 2010).…”
Section: Direct Speech In Court Interpretingmentioning
confidence: 96%
“…1.For instance, Berk-Seligson 1990Biernacka 2019;Christensen 2011;Dhami et al 2017;Fraser and Freedgood 1999;González et al 2012;Goodman-Delahunty et al 2014;Hale 1997Hale , 1999Hale , 2001Hale , 2004Jacobsen 2004Jacobsen , 2008Lee 2009Lee , 2010Lee , 2011Liu and Hale 2018;Mason 2015Mason , 2018Mason and Stewart 2001;O'Barr 1982;Rigney 1999;Teng et al 2018;Wong 2020. 2.For a detailed explanation of the research project and the findings, see Orozco-Jutorán 2018 and 2019.…”
Section: Notesmentioning
confidence: 99%
“…Despite the lack of codified standards, ongoing linguistic research in Belgian Assize Courts (Gallez 2010;Maryns 2012Maryns /2013 has revealed a tendency for judges to prefer an unwritten protocol of triadic communication: the rationale is that this maximizes transparency, maintaining important features of the client's communication -both verbal and non-verbal. According to this protocol, interpreters are encouraged to use: (a) short consecutive interpreting when addressing the court to interpret the turns of their minority language clients; and (b) simultaneous whispered interpreting for minority language clients who need to follow what is said by majority language speakers.…”
Section: Introductionmentioning
confidence: 98%